Transradial intra-aortic catheter looping in the angioplasty of severe intracranial symptomatic arteriosclerotic diseases - Xu, Gang-Qin; Xia, Jin-Chao; Cai, Dong-Yang; Yang, Bo-Wen; Zhao, Tong-Yuan; Xue, Jiang-Yu; Wang, Zi-Liang; Li, Tian-Xiao; Gao, Bu-Lang (Frontiers in Neurology, 2023)
Purpose This study aims to investigate the effect and feasibility of intra-aortic catheter looping via transradial access in angioplasty for symptomatic intracranial severe (>70%) atherosclerotic stenosis or occlusion of large arteries (SISOLAs). Materials and methods Patients with SISOLAs who underwent transradial endovascular angioplasty using the catheter looping technique in the ascending aorta were retrospectively enrolled. The clinical data and treatment outcomes were analyzed. Results Fifteen patients aged 48–71 years were enrolled in this study. Left vertebrobasilar artery occlusion was present in 1 (6.7%) patient, severe left middle cerebral artery stenosis in 7 (46.7%) patients, severe left internal carotid artery (ICA) stenosis of the ophthalmic segment in 4 (26.7%) patients, severe left ICA stenosis of the cavernous segment in 2 (13.3%) patients, and severe right middle cerebral artery stenosis in 2 (13.3%) patients. The arterial stenosis ranged from 70 to 92% (mean 86%) before stenting. The looping of a guiding catheter in the ascending aorta via transradial access for angioplasty was successful in all patients (100%). The vertebral artery intracranial segment occlusion was successfully recanalized, while severe stenosis in the remaining 14 patients was successfully eliminated. After endovascular recanalization, the residual stenosis was reduced by 12–26% (median 18%). No puncture-related complications or surgical-related neurological complications occurred in these patients. In the follow-up angiography conducted on 10 (66.7%) patients after 6–25 months, no in-stent restenosis was detected. Conclusion Intra-aortic guiding catheter looping via transradial access for endovascular angioplasty of SISOLAs is technically safe, feasible, and effective, especially when the transfemoral artery approach is difficult or impossible to undertake.